Speech accommodation toward older people in 7‐ To 12‐year‐old children. Issue 6 (20th March 2020) - Flamion, Allison; Missotten, Pierre; Goffinet, Alysson; Kukor, Léna; Nagy, Noemi; Adam, Stéphane
Abstract: From an early age, children develop stereotypes toward older adults leading to potential ageism. In young adults, ageism includes conversational changes, also known as elderspeak, characterized by louder, slower, and simplified speech. Although it has direct consequence on older adults, to date no studies have explored elderspeak in children. We invited 137 Belgian children aged 7–12 to take part in a guessing game through a dissimulated Skype session. The child had to make two female interlocutors in turn, one young (25 years old) and the other old (75), guess two different words each. During the session, children remained unaware of the real purpose of the game. Prosody, verbal fluency, and semantic content of their speech were measured using the Praat and VocabProfil software. The results, analyzed using mixed‐design ANOVA, showed that children spoke louder to the older interlocutor and tended to judge her less competent to guess words than the younger participant. When the older person was second in turn, children engaged in lengthier and more detailed explanations. Unexpectedly, positive views on older people correlated with higher voice intensity, suggesting that the child's differential vocal attitudes may reflect benevolent ageism. In conclusion, significant speech accommodation can be detected in 7‐ to 12‐year‐old children when they speak to an older compared with a younger interlocutor. This accommodation is characterized by louder voice and lengthier explanations. Abstract : During a dissimulated guessing game, children aged 7 to 12 spoke louder and used lengthier explanations when they talked to an old compared to a young interlocutor. These results are a first indication of child speech accommodation toward older people.